Ill impacts of parthenium weed on human health, livestock production and environment - S.M. Rezaul Karim (2012)
Parthenium weed (Parthenium hysterophorus L) an environmental pollutant, causing enormous losses to human health, animal health, crop production and biodiversity, in a number of countries. India and Australia are severely affected countries. Although Malaysia is not infested with this notorious weed but edaphic and climatic conditions of the country may favour to establish the weed if the peoples of the country are not alert about the invasion of the species from infested countries. Awareness must be created among the inhabitants of the countries especially in Asia Pacific region to combat the menace. Well planned research should be carried out to iradicate or to control the weed effectively in the infested countries.